Relationship between sleep and obesity among U.S. and South Korean college students - Sa, Jaesin; Choe, Siyoung; Cho, Beom-young; Chaput, Jean-Philippe; Kim, Gyurin; Park, Chae-Hee; Chung, Joon; Choi, Yoojin; Nelson, Beatrice; Kim, Yongkyu (BMC public health, 2020)
Background Little is known about the relationship between sleep and obesity in young adults, particularly college students. This study examined the relationship between sleep (i.e., sleep duration and quality) and obesity in a large and diverse binational sample of college students. Methods Analyses were based on a 40-item paper survey from 2016/2017 to 2017/2018 academic years, with a 72% response rate. The samples were 1578 college students aged 18–25 years from five universities (two in the U.S. and three in South Korea). Weight and height were measured objectively; other measures (e.g., health behaviors) were self-reported. Multinomial logistic regression was used to assess the association between sleep duration and independent variables (race/nationality, gender, and BMI). Poisson regression was used to examine the relationship between sleep quality and independent variables. Results Overall, blacks had a higher adjusted odds ratio (AOR) of short sleep (< 7 h/night) than whites (AOR = 1.74, P < .01); overweight participants had a higher AOR of short sleep than normal weight participants (AOR = 1.52, P < .01); and obese participants had a higher AORs of both short and long sleep (> 9 h/night) (AOR = 1.67, P < .01; AOR = 1.79, P < .05, respectively). Among men, being black, overweight, and obesity were associated with short sleep ( P < .05), whereas only obesity was related to short sleep among women ( P < .05). In analyses stratified by race and nationality, overweight and obesity were related to short sleep among blacks only ( P < .05). Overall, sleep quality (getting enough sleep to feel rested in the morning in the past 7 days) was worse in blacks and South Koreans than whites ( P < .05), worse in women than men ( P < .05), and worse in participants with obesity than normal weight participants ( P < .05). Conclusions Obesity was associated with both short (< 7 h/night) and long sleep duration (> 9 h/night) and poor sleep quality among all participants. In comparison with whites, blacks were more like to have short sleep, and blacks and South Koreans had worse sleep quality. Further investigations using a larger sample of college students in multiple countries may be helpful to identify target populations who are at a greater risk of obesity and sleep problems.